2013
DOI: 10.1002/bjs.9085
|View full text |Cite
|
Sign up to set email alerts
|

Causes of false-negative sentinel node biopsy in patients with breast cancer

Abstract: SLN serial sectioning contributes to a higher rate of detection of SLN metastasis. The rate of upstaging of the tumour is similar in false- and true-negative groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In addition, there were several significant baseline differences between the two groups, which in large part can be explained by the underlying selection mechanisms for the surgical methods studied. Multifocality, for example, is a known contributor to the surgical choice of mastectomy, but may at the same time represent both a risk factor for a false‐negative sentinel node biopsy and for worse prognosis. This factor, however, was not identified as an independent predictor in the adjusted analyses, which is in line with publications reporting that the type of surgery might not influence the association between multifocality and worse tumour characteristics and outcome.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, there were several significant baseline differences between the two groups, which in large part can be explained by the underlying selection mechanisms for the surgical methods studied. Multifocality, for example, is a known contributor to the surgical choice of mastectomy, but may at the same time represent both a risk factor for a false‐negative sentinel node biopsy and for worse prognosis. This factor, however, was not identified as an independent predictor in the adjusted analyses, which is in line with publications reporting that the type of surgery might not influence the association between multifocality and worse tumour characteristics and outcome.…”
Section: Discussionsupporting
confidence: 81%
“…Other risk factors such as tumor location [ 12 , 13 ] and the number of dissected SLNs [ 12 , 15 , 17 ] were also shown to be significant risk factors for a FN in other studies. Our findings are concordant with previous studies that FN results are more likely to be observed when a tumor is located in the upper outer quadrant of the breast and when only a single SLN is harvested.…”
Section: Discussionmentioning
confidence: 94%
“…There are several studies that have identified clinical factors predictive of a FN in a SLNB [ 12 - 17 ]. They mentioned tumor size, multifocal-multicentric disease, location of tumor, and number of removed SLN as risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al re-evaluate FFPE tissue blocks of SNs and undiagnosed metastases of SNs are discovered in 18% patients with metastasis at ALND or subsequent axillary recurrence. In the patients without any axillary recurrence, 11% patients have undiagnosed metastases in SNs during reevaluation [25]. Underestimation of lymph node staging is possible in SLNB.…”
Section: Discussionmentioning
confidence: 99%